PILKADES, KEPALA DESA DAN PEREBUTAN CELUK - Agus Nurhadi (At-Taqaddum, 2013)
Head of Village is still a magnet that attracts the elite at the village. They are willing to invest expensively in the election and perform social task with high cost whereas the bengkok income and monthly incentive could not cover the incurred cost. Based on the results of the election in Kalipajang, it was found that the elites who scrambled as head of village was not to maintain the ideology, and to struggle that has a value of worship as in religion or in economics as propounded by Karl Marx, but they fought to get celuk-a culture capital which is Borrowed Pieere Bourdieu’s analysis.